Analisis Kestabilan Lereng pada Blok Timur Tambang Muara Tiga Besar Utara PT. Bukit Asam Tbk, Kabupaten Muara Enim, Provinsi Sumatera Selatan - Andryan Febriadi; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT Bukit Asam Tbk is a coal mining industrial sector corporation which is located in Tanjung Enim, Sumatera Selatan. Pit of Muara Tiga Besar Utara (MTBU) utilized open pit mining system which needs a calculation and analysis of slope stability. Slope stability analysis was used to find out the actual condition of this slope area and to evaluate sequence design of mining plan. This slope stability analysis applied limit equilibrium method (Morgenstern-Price) and Monte Carlo’s simulation for probabilistic analysis. Then sensitivity analysis is also performed to find out the influential parameter in slope stability. In this research, the slope stability was conducted by implementing A-A’ and B-B’ cross sections which represent the condition of highwall, lowwall and sidewall. Results of slope stability based on the actual topography condition were FS 1.34 and PF 1.9% for overall slope highwall, FS 2.28 and PF 0% for overall slope lowwall, FS 1.89 and PF 0% for overall slope sidewall. Then, the result of sensitivity analysis showed that saturated density parameter, phi and water table are the influential parameter to the slope stability. Meanwhile, cohesion doesn't have any significant influence. The result of probability and sensitivity analysis obtained that slope is safe and appropriate with slope stability threshold value. Keywords: MTBU, Slope stability, Probability analysis, Morgenstern -Price, Monte Carlo